SEARCH SMALL BODIES IMAGES IN COLLECTIONS DIGITIZED PHOTOGRAPHIC OBSERVATIONS OF PREVIOUS YEARS - Shatokhina, S.; Kazantseva, L.; Kazantsev, A.; Andruk, V.; Golovnia, V. (Одеські астрономічні публікації, 2016)
Photographic observations of XX century is an important source of information on small bodies of the Solar system. The observations of chronologically earlier oppositions, photometric evaluation of brightness for long periods of time allow refining the orbits of asteroids and identifying various non-stationaries. Unfortunately international databases were contained a very little observable data for accurate estimates of geometric and kinematic parameters of asteroids. We analyzed the results of digital processing of 338 photographic plates of Northern Sky Survey (FON) project. Modern approach to processing early observations using new digital technologies provides a sufficiently high accuracy of coordinates and magnitudes for all objects on astroplates. As a result 570 images of asteroids and 4 images of comets from 8-16 magnitudes were detected on these plates. Equatorial coordinates and stellar magnitudes of them were composed to catalog of asteroids. All positions were compared with ephemeris. Analysis of ephemeris calculations with known today about the several hundred small planets with observation data showed some interesting results.